Fatal Palbociclib -Related Interstitial Pneumonitis - MD, Levy Ofer; MD, Ptashkin Ekaterina; MD, Shechtman Yitzhak; MD, Tamar Kass; MD, Natif Noam; MD, Sanset Sofia; MD., Katz Daniela (Archives of Clinical and Medical Case Reports, 2019)
Palbociclib is indicated in combination with an aromatase inhibitor for first line treatment of hormone receptor-positive, human epidermal growth factor receptor 2 (HER2)-negative advanced or metastatic breast cancer. We report a case of a 71-year-old patient with metastatic breast cancer who developed fatal diffuse parenchymal lung injury three months after the initiation of palbociclib plus letrozole. The patient presented with pulmonary embolism, which masked the progression of diffuse parenchymal lung injury. As dyspnea worsened, chest CT revealed a mixed pattern of severe interstitial and alveolar lung injury. Transbronchial lung biopsy was consistent with the subacute lung injury pattern. Treatment with high dose glucocorticoids did not result in clinical improvement and the patient succumbed to respiratory failure. It is important for clinicians to be aware that fatal interstitial pmeumonitis may occur in patients who are treated with palbociclib because early diagnosis may be vital.